Role of religion in the promotion of transplantation and organ donation - Golebiowska, Maria; Golebiowska, Beata; Chudzik, Robert; Jarosz, Katarzyna; Klatka, Maria (Journal of Education, Health and Sport, 2017)
Religion and tradition are one of the most influential factors shaping the lives of many communities, which can often be seen in social debates on medical ethical dilemmas. Transplantology, as field of medicine that allows full recovery of health and a second chance of fate by patients in last stages of organ failure, is also the source of numerous moral dilemmas associated with religious beliefs. The purpose of this study is to present the relationship between religiousness, religious views and transplantation, as well as the role of religion in the promotion of informed consent for transplantation and the spread of knowledge about transplantation. Numerous studies indicate the influence of religiosity and membership to the religious community on the expression of conscious consent to donate organs after death. Religiosity predisposes to greater opposition towards organ donation and transplantation comparing to the population of non-religious claimants. Between religious communities, Catholics are more willing to express their informed consent than other religions believers. The involvement of religious leaders and religious communities in public health debates is associated with significant changes in public awareness of transplantation, indicating the importance of further research in this regard.